Hydrothermal transformations in an aluminophosphate glass matrix containing simulators of high-level radioactive wastes - Yudintsev, S. V.; Mal’kovsky, V. I.; Mokhov, A. V. (Doklady earth sciences, 2016)
The interaction of aluminophosphate glass with water at 95°C for 35 days results in glass heterogenization and in the appearance of a gel layer and various phases. The leaching rate of elements is low owing to the formation of a protective layer on the glass surface. It is shown that over 80% of uranium leached from the glass matrix occurs as colloids below 450 nm in size characterized by high migration ability in the geological environment. To determine the composition of these colloids is a primary task for further studies. Water vapor is a crystallization factor for glasses. The conditions as such may appear even at early stages of glass storage because of the failure of seals on containers of high-level radioactive wastes. The examination of water resistance of crystallized matrices and determination of the fraction of radionuclide in colloids are also subjects for further studies.